In-vitro steady and pulsatile flow studies in saccular aneurysm models using particle image velocimetry (PIV) : with effects of stents and springs - Zhao, Jian Bing. (2009)
Rupture of the cerebrovascular aneurysm will result in brain haemorrhage which carries a very high morbidity. It is therefore important to understand the haemodynamic factors which may play a role in the formation, development and rupture of the cerebrovascular aneurysm. The factors may be derived from the information of the local velocity vectors, wall shear stress and pressure. The obtained database will also be useful for validating theoretical models and any proposed treatment methods.